PRESUPPOSITION OF THE MAIN CHARACTER’S UTTERANCES IN BATAK TOBA MOVIE ALANI HAPOGOSON - CHINDY CHINTYA PANGGABEAN; MORADA TETTY; FERIYANTI ELINA GULTOM (LINGUISTICA, 2022)
The research was found on the topic about Presupposition of the Main Character’s Utterances in Batak Toba Movie Alani Hapogoson. This study was aimed at identifying the types of presupposition, most dominant type and to elaborate the realization of the types of presupposition by the main character in Alani Hapogoson movie.. The study was conducted by using descriptive qualitative method. The source of data was taken from the utterances of the main character’s utterances in batak toba movie alani hapogoson. The technique for analyzing the data is descriptive qualitative research based on Creswell’s theory. The result of this research was types of presupposition can be found in Alani Hapogoson movie are existensial (34%), Factive (26%), Lexical (10%), Structural (14%), Non-factive (2%), and Counterfactual (14%). The dominant type of presupposition that used by main character utterances was existensial presupposition, because used utterances formed by proper names, noun phrase and possesive to show the existence of someone.